Women's movement in postcolonial Indonesia : gender and nation in a new democracy - Martyn, Elizabeth, 1968- (New York, NY : RoutledgeCurzon, 2005)
Examines women's activism in the early years of independent Indonesia when new attitudes to gender, nationalism, citizenship and democratisation were forming.
Book Cover; Title; Contents; List of figures; Acknowledgements; Introduction; Alternative approaches to education; Education what for?; Small alternative schools; Steiner Waldorf education; Montessori education; Democratic schools; Other philosophies, other schools; Doing it yourself; Setting up a small school or learning centre; Home-based education; Flexible schooling; Alternative approaches in the state system; State schools: alternative ways of working; Small is beautiful: lessons from America; Parents as change agents; Conclusion; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Women -- Indonesia -- History -- 20th century; Feminism -- Indonesia -- History -- 20th century; Femmes -- Indonésie -- Histoire -- 20e siècle.; Féminisme -- Indonésie -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Women's Studies; Feminism; Women; Indonesia; 1900-1999; Electronic books; History